2014
DOI: 10.1002/2014gl060777
|View full text |Cite
|
Sign up to set email alerts
|

Winter/summer mesopause temperature transition at Davis (69°S) in 2011/2012

Abstract: We present quasi‐continuous measurements of temperature profiles in the Southern Hemisphere mesopause region during the transition from winter to summer conditions in 2011/2012. In a period of 120 days around solstice, we have performed iron lidar observations at Davis (69°S), Antarctica, for a total of 736 h. The winter/summer transition is identified by a downward shift of the mesopause which occurs on 8 November 2011. Soon after transition, mesopause heights and temperatures are similar to the Northern Hemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 19 publications
2
17
0
Order By: Relevance
“…Lübken et al (2014) showed that the timing of the zonal wind decrease associated with the stratospheric polar vortex breakdown in spring was consistent with the onset of polar mesospheric clouds (PMC), and the temperature decrease around the mesopause. These authors proposed that the simultaneous changes in the two separate height regions could be explained by an increase in the eastward forcing by GWs that can propagate into the mesosphere after the stratospheric winds have weakened; however, they did not show observational evidence of the GW modulation.…”
Section: Critical Level Filtering In the Vertical In The Stratospherimentioning
confidence: 83%
“…Lübken et al (2014) showed that the timing of the zonal wind decrease associated with the stratospheric polar vortex breakdown in spring was consistent with the onset of polar mesospheric clouds (PMC), and the temperature decrease around the mesopause. These authors proposed that the simultaneous changes in the two separate height regions could be explained by an increase in the eastward forcing by GWs that can propagate into the mesosphere after the stratospheric winds have weakened; however, they did not show observational evidence of the GW modulation.…”
Section: Critical Level Filtering In the Vertical In The Stratospherimentioning
confidence: 83%
“…In subsection 4.2 we will use these observations to provide an explanation for the unique temporal variation of the mesopause at Antarctic latitudes. Note that some related observations have been published before (Kirkwood et al, 2008;Karlsson et al, 2011;Benze et al, 2012;Morris et al, 2012;Lübken et al, 2014;Viehl et al, 2015).…”
Section: Introductionmentioning
confidence: 90%
“…High resolution temperature measurements by resonance lidar have recently revealed that in mid summer at Davis (69 • S) the altitude of the mesopause increases within a few days and its temperature decreases substantially compared to the standard northern hemisphere values of 88 km and 130 K, respectively (Lübken, 1999;Lübken et al, 2014Lübken et al, , 2015. Model results indicate that this phenomenon is related to the circulation in the stratosphere coupled to the mesosphere by the transmission of gravity waves (see, e.g., Becker et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Kirkwood et al . [] and subsequent studies [e.g., Lübken et al ., ] indicated that the PMSE detection in the SH usually starts at high altitudes and descends gradually with time. Such a feature is observed in the 2014/2015 and 2015/2016 seasons but not in 2013/2014.…”
Section: Polar Mesosphere Summer Echoes Over Three Summer Periods In mentioning
confidence: 99%